Online inverse optimal control for control-constrained discrete-time systems on finite and infinite horizons. (October 2020) - Molloy, Timothy L.; Ford, Jason J.; Perez, Tristan
Abstract: In this paper, we consider the problem of computing parameters of an objective function for a discrete-time optimal control problem from state and control trajectories with active control constraints. We propose a novel method of inverse optimal control that has a computationally efficient online form in which pairs of states and controls from given state and control trajectories are processed sequentially without being stored or processed in batches. We establish conditions guaranteeing the uniqueness of the objective-function parameters computed by our proposed method from trajectories with active control constraints. We illustrate our proposed method in simulation.